(untitled) (Academicia Globe: Inderscience Research, 2023)
This article describes the concept of creativity in different ways information about views and approaches is provided. In addition, the article presents the importance of creativity in elementary school mathematics classes, ways and factors of creativity stimulation, and methods of its evaluation.